2022
DOI: 10.3233/ch-221540
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal ultrasound imaging with conventional B-mode, elastography, and parametric analysis of contrast-enhanced ultrasound (CEUS): A novel approach to assess small bowel manifestation in severe COVID-19 disease

Abstract: The aim was to describe the small bowel morphology with conventional B-mode and elastography and additionally to evaluate dynamic effects of COVID-19 associated small bowel microvascularization using CEUS with color coded perfusion parameters. Thirteen patients with severe COVID-19 acute respiratory distress syndrome (ARDS) were investigated. 13 patients required intensive care treatment with mechanical ventilation. Five patients required extracorporeal membrane oxygenation (ECMO). Contrast-enhanced ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Loss of RBC deformability and/or increased aggregability favors the development of thrombotic processes in the microcirculation [18,52]. This has previously been described in COVID-19 patients [10,53], especially when platelets are also activated [54][55][56]. Loss of RBC deformability and/or increased aggregability favors the development of thrombotic processes in the microcirculation [18,52].…”
Section: Influence Of Sarscov-2 On Red Blood Cell Functionmentioning
confidence: 79%
See 1 more Smart Citation
“…Loss of RBC deformability and/or increased aggregability favors the development of thrombotic processes in the microcirculation [18,52]. This has previously been described in COVID-19 patients [10,53], especially when platelets are also activated [54][55][56]. Loss of RBC deformability and/or increased aggregability favors the development of thrombotic processes in the microcirculation [18,52].…”
Section: Influence Of Sarscov-2 On Red Blood Cell Functionmentioning
confidence: 79%
“…Loss of RBC deformability and/or increased aggregability favors the development of thrombotic processes in the microcirculation [18,52]. This has previously been described in COVID-19 patients [10,53], especially when platelets are also activated [54][55][56].…”
Section: Influence Of Sarscov-2 On Red Blood Cell Functionmentioning
confidence: 83%
“…The parametric imaging CEUS potential has also been explored by Tews H. et al in patients with severe COVID-19 disease to evaluate the presence of small bowel barrier disruption or microemboli. They found two subsets of patients, one showing early contrast enhancement in the bowel wall layers probably as an expression of systemic inflammation, and the other showing delayed contrast enhancement as an expression of microembolization-related hypoperfusion [66].…”
Section: Contrast-enhanced Ultrasound (Ceus)mentioning
confidence: 99%
“…Investigations were conducted on 13 patients who had severe acute respiratory distress syndrome (ARDS) caused by COVID-19. In conclusion, it was demonstrated that the small bowel may also be a critical interaction location in COVID-19 [29]. antibiotics, systemic acyclovir, and photo biomodulation therapy (PBMT) were recommended for oral lesions [30].…”
Section: Effect Of Sars-cov-2 On Thrombotic Processes In the Whole Bo...mentioning
confidence: 99%